Politeness in Thesis Consultation by WhatsApp: Do Lecturers and Students Apply Different Strategies? - Pasaribu, Arsen Nahum; Saragih, Erikson; Gea, Agustinus (Universitas Lancang Kuning, 2022)
The study of politeness in education setting interaction has increased in last decades. However, the investigation of politeness strategies in lecturer-student interaction using WhatsApp is relatively unexplored. Therefore, this study aims to explore politeness strategies used by a lecturer and students in virtual communication using WhatsApp during thesis consultation. The researcher applied a mixed method: qualitative and quantitative research to discover the politeness phenomena in WhatsApp interaction. The participants of the study were 10 undergraduate students of English Department, University of HKBP Nommensen, and a lecturer as their thesis consultant. The data of the study consist of 50 screenshots of WhatsApp chats thesis consultation. The results show that all four types of politeness strategies were found in lecture-students interaction. The politeness strategies used by the lecturer and students differ greatly. The lecturer dominantly employed bald on-record (30. 93%) with the most imperative sentences realization; on the other hand, the students tend to use positive politeness strategy (23.20%) with the most greetings realization. This demonstrates that lecturers keep their distance when communicating, whereas students attempt to “get closer” during the interaction. The different politeness strategy choices are caused by the different power and social status (position) factors between lecturers and students. The findings of this study also show that the politeness strategies chosen by lecturers and students are not always consistent with previous similar studies.